Evaluation of epidemiology, safety, and complications of male circumcision using conventional dissection surgery: experience at one center - Moslemi, Mohammad Kazem (Dove Medical Press, 2011)
BACKGROUND: Circumcision can be performed for a variety of techniques, including conventional dissection surgery or a Plastibell device, and has religious, ritual, or medical roots. In countries like Iran, circumcision is done purely on religious grounds. In this study, we outline 390 cases in our practice and describe the epidemiology, indications, surgical technique used, and the early complications. MATERIALS AND METHODS: In this retrospective study, the charts for 390 circumcision cases were analyzed for the period March 2005 to August 2010. We reviewed all cases, noting age, indication, type of anesthesia used, technique, cosmetic appearance, and any potential early complications. All cases were followed up 1–4 weeks postoperatively and their notes were evaluated. RESULTS: The age of children who underwent circumcision ranged from 3 weeks to 14 years, with a mean age of 4.25 years. The most common age for circumcision was 4–5 years (14.6%), and the least common age was 11–12 years (1.5%). In 372 cases (95%), the parents had opted for the procedure for religious reasons, and in 18 cases (5%), there was a medical indication, including phimosis (11 cases, 3%), urinary tract infection (5 cases, 1.2%), and balanoposthitis (2 cases, 0.8%). No major early complications were found in our series. Cosmetic appearance was satisfactory in all cases by 4 weeks after the operation. CONCLUSION: Circumcision was performed for religious reasons in our cases, although medical indications sometimes modified the timing of the procedure. Conventional dissection surgery for circumcision was safe, effective, and without any major complications.